2020
DOI: 10.1148/radiol.2020200323
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Posttreatment Chest CT Findings: 2019 Novel Coronavirus (2019-nCoV) Pneumonia

Abstract: pharyngeal swab was positive for 2019-nCoV nucleic acid 2 days after hospitalization.After the patient received 7 days of treatment, combined with interferon inhalation, real-time fluorescence polymerase chain reaction of the patient's pharyngeal swab became negative for 2019-nCoV nucleic acid. At 7 days, chest CT showed decreasing ground-glass opacities (Figure b). At day 13 after admission, the ground-glass opacities in the right lung had resolved; the left ground-glass opacities showed partial resolution (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
87
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 2 publications
16
87
0
4
Order By: Relevance
“…Also, bilateral multilobe involvement was dominant in stages 2, 3 and 4. Similar to some case reports (23,24), it can be concluded that chest CT (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Grading the Quality Of Evidencesupporting
confidence: 58%
“…Also, bilateral multilobe involvement was dominant in stages 2, 3 and 4. Similar to some case reports (23,24), it can be concluded that chest CT (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Grading the Quality Of Evidencesupporting
confidence: 58%
“…The latency period of this disease is 1e14 days, mostly 3e7 days. 3,4 The clinical manifestations are mainly fever and fatigue, but some patients may also be asymptomatic virus carriers, with mild-onset symptoms and no fever.…”
Section: Discussionmentioning
confidence: 99%
“…They are mainly distributed underneath the pleura with uneven density. These CT manifestations reflect the pathological process of lung injury in patients with viral pneumonia 3,4 and the distribution of most of the lesions are in the peripheral zone of the lungs, peripheral bronchus, and alveoli. This distribution may be related to the infection mode of viral pneumoniadrespiratory droplet transmission.…”
Section: Chest Ct Imaging Features Of Covid-19mentioning
confidence: 99%
“…The study by Song et al (42) concluded that greater consolidation indicated disease progression. Some case reports showed that smaller size, extent, and absorption of these lesions indicate the improvement (32,42,(51)(52)(53). Tables Table 1: The suspected case with typical imaging findings of pneumonia (only for Hubei)…”
Section: The Value Of Radiology In Prevention and Control Of Covid-19mentioning
confidence: 99%